2014
DOI: 10.5009/gnl.2014.8.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemia in Patients with an Amebic Liver Abscess

Abstract: Background/AimsMany parasites induce changes in the lipid profiles of the host. Cholesterol increases the virulence of Entamoeba histolytica in animal models and in vitro culture. This study aimed to determine, in patients with an amebic liver abscess, the correlation between cholesterol and other features, such as the size and number of abscesses, standard hematological and serum chemistry profiles, liver tests, and duration of hospital stay.MethodsA total of 108 patients with an amebic liver abscess and 140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…21 Cholesterol is generally low and corresponds with what was previously reported by our group, probably because trophozoites lack enzymes to synthetize cholesterol and fatty acids, which are scavenged from the host. 22,23 The altered laboratory values in patients with ALA correspond to those reported in the literature. 24,25 Northeastern Mexico is an area with endemic amoebiasis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…21 Cholesterol is generally low and corresponds with what was previously reported by our group, probably because trophozoites lack enzymes to synthetize cholesterol and fatty acids, which are scavenged from the host. 22,23 The altered laboratory values in patients with ALA correspond to those reported in the literature. 24,25 Northeastern Mexico is an area with endemic amoebiasis.…”
Section: Discussionsupporting
confidence: 82%
“…This group also had altered laboratory results, showing low levels of haemoglobin, haematocrit and albumin, which may be due to poor nutrition in people with low socioeconomic status, and can be exacerbated by the consumption of alcoholic beverages 21 . Cholesterol is generally low and corresponds with what was previously reported by our group, probably because trophozoites lack enzymes to synthetize cholesterol and fatty acids, which are scavenged from the host 22,23 . The altered laboratory values in patients with ALA correspond to those reported in the literature 24,25 …”
Section: Discussionsupporting
confidence: 80%
“…To date, it has not been proposed a mechanism on how E. histolytica could be involved in hypocholesterolemia, however, paradoxically, it is well-known that trophozoites grown in medium with high levels of cholesterol present an increased virulence (Olivos et al, 2005;Serrano-Luna et al, 2010). The cholesterol flux in mammalian host is throughout the entero-hepatic circulation, and, E. histolytica invades the liver by the same pathway, suggesting that the parasite colonizes cholesterol enriched organs, as described previously (Flores et al, 2014).…”
Section: Lipids Alteration In Patientsmentioning
confidence: 70%
“…INFECTED WITH E. histolytica E. histolytica pathogenesis causes intestine damage associated with chronic inflammation, mucosal disruption, altered barrier integrity, and dysbiosis that compromise the correct nutrient absorption and provokes other pathologies: (i) become patients more susceptible to other chronic infections (Korpe and Petri, 2012), (ii) increase the possibilities to alter the microbiota and eukaryome in the intestine, (iii) 93% of patients with amoebic liver abscess (ALA) present changes in serum lipid profiles, mainly hypocholesterolemia, (iv) some studies have found abnormal cephalin-cholesterol flocculation test (Viranuvatti et al, 1963;Gujral et al, 1982;Flores et al, 2014;Filippas-Ntekouan et al, 2017) and significantly lower levels in the lipid profile in infected patients with ALA (Bansal et al, 2005), (v) triglycerides and cholesterol increase in the liver of hamsters infected with E. histolytica trophozoites, but animals show hyperlipidemia and hypocholesterolemia (Gujral et al, 1982). However, further research efforts need to be focused to better understanding the molecular mechanism on cholesterol alterations and lipid homeostasis changes during trophozoite infection.…”
Section: Lipids Alteration In Patientsmentioning
confidence: 99%
“…The organism is rich in phospholipases and lysophospholipase essential for cytolysis of cells [ 40 ]. Hypocholesterolemia has been recorded in patients with ALA [ 41 ]. Fatty Liver is high in intracellular triglycerides and is an organ active in the production of cholesterol.…”
Section: Amoebic Liver Abscess and Alcoholmentioning
confidence: 99%